Comparison of chlorine dioxide and chlorhexidine 2% antiseptic in reducing bacterial colony counts as an alternative to DUWLs cleaning: a quasi-experimental study - Elfiyatinnufus, Rifqiyah; Mulyanti, Sri; Utami, Ulfah; Malinda, Yuti; Laut, Deru Marah (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: The inner surfaces of dental unit waterlines (DUWLs) possess an accumulation of any bacteria. Microorganisms can enter dental unit waterlines from water reservoirs. Antiseptics are substances that inhibit the growth of bacteria. Chlorine dioxide is effective in decontaminating microbes in the DUWLs and has a beneficial effect on reducing nosocomial infections. Chlorhexidine effectively prevents the growth of Streptococcus bacteria. The addition of antiseptic agents to the water source contributed to a significant reduction of the cultivable microbial counts in the aerosol. The purpose of this study was to analyze the difference between Chlorine Dioxide 0,1% and Chlorhexidine 2% antiseptics on the number of bacterial colonies in the Dental Unit Waterline. Methods: This study was a quasi-experimental study with a total sample size of 8 dental units that have water tanks in the oral surgery clinic. The sampling technique was total sampling, where the sample was divided into 2 groups, group I using Chlorine Dioxide and group II using 2% Chlorhexidine calculation of colony counts unit using the plate count method. Results: The difference in the number of colonies before being given Chlorine Dioxide was 13,153 CFU/mL and after being given Chlorine Dioxide antiseptic was 6,070 CFU/mL, while before being given 2% Chlorhexidine antiseptic was 12,917 CFU/mL and after being given 2% Chlorhexidine antiseptic was 2,823 CFU/mL. There is a significant difference in the number of bacterial colonies before and after being given Chlorine Dioxide and Chlorhexidine 2% antiseptic with ρ=0.001; Conclusion:  Chlorhexidine 2% reduces bacterial colony forming unit in DUWLs much more than using Chlorine dioxide for the alternative of DUWLs Cleaning Agents.Keywords: DUWLs, chlorine dioxide, chlorhexidine 2%, bacterial colony counts